Determination of Geochemical Bio-Signatures in Mars-Like Basaltic Environments - Olsson-Francis, Karen; Pearson, Victoria K.; Steer, Elisabeth D.; Schwenzer, Susanne P. (Frontiers in Microbiology, 2017)
Bio-signatures play a central role in determining whether life existed on early Mars. In this study, we used a combination of experimental microbiology and thermochemical modelling techniques to identify potential geochemical bio-signatures for life on early Mars. Laboratory experiments were used to determine the short-time effects that biota had on basalt dissolution and the formation of secondary alteration minerals; whilst the thermochemical modelling (code CHIM-XPT, M. H. Reed, University of Oregon) was used to predict growth of secondary alteration minerals, which can be used as bio-signatures, over a geological timescale. For the biotic experiments heterotrophic bacterium, Burkholderia sp. strain B_33, was grown in a minimal growth medium with basalt as the sole nutrient source. No growth was detected in the absence of the basalt. During exponential growth, the pH decreased rapidly from pH 7.0 to 3.6 and then gradually increased to a steady-state of equilibrium of between 6.8 and 7.1. Microbial growth coincided with an increase of key elements in the growth medium (Si, K, Ca, Mg and Fe). We modelled the dissolution of the basalt in very dilute brine at 25 °C, 1 bar; the pH was buffered by the mineral dissolution and precipitation reactions. In the model, we assumed complete dissolution of the rock into solution. Preliminary results suggested that at the water to rock ratio of 1 x 107; zeolite, hematite, chlorite, kaolinite and apatite formed abiotically. The biotic weathering processes were modelled by varying the pH conditions within the model to adjust for biologic influence. This study suggests that for a basaltic system the microbial mediated dissolution of basalt would result in ‘simpler’ secondary alteration, consisting of Fe-hydroxide and kaolinite, under conditions where the abiotic system would form chlorite in addition to Fe-hydroxide and kaolinite. The results from this study demonstrate that, by using an experimental and theoretical approach, it is possible to identify secondary alteration minerals that could potentially be used to distinguish between abiotic and biotic weathering processes on early Mars. This work is crucial for interpreting data from past, present and future life detection missions to Mars.